Geochemistry of Geothermal Hotspring in Perak (CWS) - Tuan Salim, Tengku Hasnul Hadi (Universiti Teknologi PETRONAS, 2010)
This document basically contains the general overview of the project titled "Geochemistry of Geothennal hot spring in Perak (CWS)". Before the study started, the research should be done ftrst in order to get the general idea on what is the research is all about in general. This report consists of background of study, problem statement, objectives and scope of study and also some literature review. Chemical analysis will be done on the hot spring water to determine the chemical content in the water before it can be use as drinking water. The goal of this analysis is to detennine either the water is safe as drinking water. Basically in order to do the analysis, two common equipment can be use which are Atomic Absorption Spectrophotometry (AAS) and Inductively Coupled Plasma (ICP). In Malaysia, hot spring water is very high in Hidrogen Sulphide and cause faint smell. Hydrogen sulftde is considered a broad-spectrum poison, meaning that it can poison several different systems in the body, although the nervous system is most affected. Hydrogen Sulphide is a potent chemical asphyxiant, combining with haemoglobin in red blood cells and with intracellular cytochromes and thus rapidly stopping oxygen from access to cellular metabolism (just like gases such as carbon monoxide and hydrogen cyanide). Indeed H2S is arguably as toxic as Hydrogen Cyanide HCN. Biological monitoring or tests for intoxication could be undertaken through spectrophotometry of the haemoglobin in blood.